A history of Artificial Intelligence / Tang Su Ai - Tang, Su Ai (2004)

(untitled)
The history of Artificial Intelligence (Al) Website is a dynamic web-based one stop centre that offer comprehensive information about the history of Artificial Intelligence. It provides an efficient method of information searching and browsing with contemporary and attractive user-friendly and hypermedia-based user interface design. On the maintenance side, the information is well organized in a way that the web administrator can easily add on or modify the website effortlessly. The primary objective of the website arc to gather all the in formation related to the history of AI and provide a comprehensive source as well as a centralized repository of information to store history of AI. This is to provide a complete website that the Internet users can gain and learn more on increasingly popular field of AI. Functions that are provided by the website include searching capability that allow users to quickly locate the information the users are looking for. Users can also browse for the history of AI according to researcher, fields or in chronological order. A recent event section is provided to place all the recent events or developments of AI. Other miscellaneous sections are introduction of AI, about the website, etc. All the information on the website is created in hypermedia format. Overall, at the end of the development cycle, developing this website will be helpful and practical in promoting the ever expanding knowledge of Artificial Intelligence to the World Wide Web users.